The transfer of values in families of genealogists - Jurczyk-Romanowska, Ewa (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2018)
Genealogy has particular importance for Polish people, which is the result of Polish history and the fact that the country has changed its borders a number of times; it has been invaded and occupied, and Poles were subject to forced replacement, exile, repatriation, and emigration. Numerous Polish families have their roots in many countries, and the information about their heritage is held in the archives of a number of countries. Genealogical investigations become a common passion of entire families, which, at the same time, makes it possible to observe a clear and specific transmission of values in the families of genealogues. In the conducted research the following questions were formulated: What values are perceived as particularly important in the families of genealogues? How are they preserved? In the qualitative research the form of a short essay was employed. The essays were written by members of the families of genealogues. In the families of genealogues such values as a sense of belonging and identity, taking care of the image of the family, as well as a sense of “being needed” among the older generations, a sense of security among the adults, and common family adventure among children are clearly outlined. The values conveyed in family stories are a bond that connects representatives of different generations. Common goals in the care of the image of the family, nurturing a sense of belonging and identity guide both generations of the elderly and younger. The implementation of these goals also leads to mutual learning and strengthening the sense of individual value of family members.
Keywords: migration of Poles; genealogy; intergenerational transfer of values